2005
DOI: 10.1016/j.socscimed.2004.12.014
|View full text |Cite
|
Sign up to set email alerts
|

‘MMR talk’ and vaccination choices: An ethnographic study in Brighton

Abstract: In the context of the high-profile controversy that has unfolded in the UK around the measles, mumps and rubella (MMR) vaccine and its possible adverse effects, this paper explores how parents in Brighton, southern England, are thinking about MMR for their own children. Research focusing on parents' engagement with MMR has been dominated by analysis of the proximate influences on their choices, and in particular scientific and media information, which have led health policy to focus on information and educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 19 publications
4
140
0
2
Order By: Relevance
“…Social science research has shown that vaccination decision-making should be understood in a broader sociocultural context. 25,[46][47][48] In fact, vaccination is part of a "wider social world" 49 which means that different factors (past experiences with health services, family histories, feelings of control, conversations with friends, etc.) can influence the decisionmaking process regarding vaccination.…”
Section: Potential Causes Of Vaccine Hesitancymentioning
confidence: 99%
See 2 more Smart Citations
“…Social science research has shown that vaccination decision-making should be understood in a broader sociocultural context. 25,[46][47][48] In fact, vaccination is part of a "wider social world" 49 which means that different factors (past experiences with health services, family histories, feelings of control, conversations with friends, etc.) can influence the decisionmaking process regarding vaccination.…”
Section: Potential Causes Of Vaccine Hesitancymentioning
confidence: 99%
“…This theory is based on a view of the immune system as an individual characteristic needing individualized healthcare and on the idea that there is a possible risk of immune overload due to individual "weakness" of a child. 49,127 As Casiday has shown in her qualitative study on parental measles, mumps and rubella (MMR) vaccination decision-making, this view often implies a "holistic notion of the immune system, (…) in which the immune system is viewed as central to the body's overall health, but is itself intricate and delicately balanced; it must be maintained so that it can flexibly and effectively cope with a multitude of challenges from the environment." 48 From this point of view, vaccines are seen as something that would perturb rather than boost the immune system.…”
Section: Perceptions Of the Importance Of Vaccination In Maintaining mentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the teenagers in this study are often of age, as teenagers their parents still had a large impact on their decision. The conclusion is that parents' influence over children's vaccinations and importance of personal experiences reported by Poltorak et al (2005) and Ideland (2007) also seems to be valid for adolescents. But the fact that six of the seven students in the study vaccinated themselves indicates that the consideration of the effects of the disease has been important to the students.…”
Section: Discussionmentioning
confidence: 92%
“…The precautionary principle is often emphasized. Mike Poltorak et al (2005) found how important different personal histories are in determining the willingness to vaccinate one's children against MMR (mumps, measles, and rubella). These histories include parenthood experiences, knowledge, ways of validating and engaging with information and expectations of health professionals.…”
Section: Risk and Vaccinationsmentioning
confidence: 99%